PENGEMBANGAN EKOSISTEM KEWIRAUSAHAAN PERTANIAN : SEBAGAI UPAYA REGENERASI PETANI MUDA DI JAWA BARAT - Mukti, Gema Wibawa; Kusumo, Rani Andriani Budi; Charina, Anne (Universitas Galuh, 2023)
This study aims to identify entrepreneurship's various strengths and weaknesses in agricultural youth. Furthermore, this study also aims to use the strengths to minimize the various negative impacts of the weaknesses of young farmers to help form a productive, conducive and collaborative agricultural entrepreneurship ecosystem. The research method in this article uses a systems analysis approach, statistical analysis and SWOT. System analysis is used to analyze the advantages and disadvantages of horticulture farming business actors in West Java so that the competitive advantages of young farmers can be determined. SWOT analysis is used to identify the strengths, weaknesses, opportunities and challenges of the horticultural farming environment so that it can describe the entrepreneurial development of profitable young farmers in the agricultural sector. Interaction analysis is expected to help young farmers understand problems and solutions for their business development. In the process, these factors are grouped into 8 (eight) strategic areas, which can be a guide for young farmers in carrying out their business processes, starting from the phase start, surviving until the increase in business scale. This strategy is expected to create a more productive, conducive and collaborative agricultural entrepreneurship ecosystem to become a forum that can attract the younger generation's attention to work, work and excel in the agricultural sector.